Modal Sosial Dewan Adat Dayak (Dad) Kabupaten, Dalam Melestarikan Kearifan Lokal Di Kabupaten Lamandau, Provinsi Kalimantan Tengah - Nina Putri Hayam Dey; Brian L. Djumaty (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2019)
Based on the phenomenon in the field, there are a lot of local wisdom of Tomun Lamandau Dayakpeople who are almost extinct due to the entry of modernization and the lack of public awarenessin maintaining their wisdom. Based on the results of observations and interviews found somelocal wisdom that is almost gone, namely: traditional games, traditional farming systems, wisdomrespecting the forest, traditional medicine system, spiritual abilities, traditional singing anddancing, one of which is Babukung dance (a procession of tribal death rituals of Dayak Tomun).Departing from the problem, the aim of this study was to find out and analyze the role of SocialCapital (bonding, bridging, networking) of the Dewan Adat Dayak in preserving local wisdom inLamandau District, Central Kalimantan Province. This study uses descriptive qualitativemethodology. Using snowball sampling technique in determining informants. The conclusionsdrawn in this study are: a). The social capital owned by the DAD district of Lamandau in bonding,bridging and networking is inseparable from the role of the actor, namely the head of the DistrictDAD as a driving actor. b). With the existence of social capital owned, it is expected that DAD inthe future will be more consistent in preserving existing local wisdom.